Application of a concept of a cognitive factor in managerial decision-making and planning - Naplyokov , Yuriy (Theory and Practice of Public Administration, 2026)
The article examines application of a concept of a cognitive factor in the operational planning process under conditions of a complex and dynamic environment. The main focus is on analyzing the mission and identifying the problem under resource constraints. NATO’s core operational planning doctrines and national doctrines of NATO member states such as AJP-5, COPD and JP 5-0 define operational factors such as time, force, space, and information, but do not take the cognitive factor into account. The necessity of applying the concept of the cognitive factor as an operational factor to ensure effective operational planning for the joint employment of military forces and assets with non-military capabilities has been theoretically substantiated. The concept of the cognitive factor is an integral part of the managerial decision-making process; failure to take it into account may lead to an incorrect identification of the problem, to misidentifying the opposing party as the one causing the problem, and to the failure to develop the optimal solution to the problem. The cognitive factor is archetypal in nature, relatively stable, and can be shaped by values, beliefs, national and organizational cultures, decision-making cultures, mental models, doctrines, and rules. It has been determined that the concept of the cognitive factor integrates the factors of time, force, space, and information into a unified whole in the operational planning process; in particular, it facilitates forming a systematic understanding of the current state of the environment and the social system, visualizing their dynamic development and a desired future state, analyzing the problem, and developing solutions to it. It is proposed to apply the concept of the cognitive factor in the operational planning process at the doctrinal level in conjunction with the operational factors of time, force, space, and information. It can help to improve effectiveness of operational planning and establish decision dominance under the martial law.